Outlook for the marine container shipping industry part ii : shipping microeconomics - the new generation of vessels and the implications - Huang, Yuling. (2012)
Maersk’s announcement of orders for 18,000TEU ships was a clear signal to declare war by increasing their market share and driving out smaller players. The perceived cost savings associated with the ever increasing size of containerships could be an effective ‘game changer’. The size increment of containerships is a trend that major container shipping companies cannot ignore to compete effectively. With today’s order book dominated by vessels above 10,000TEU, there is an increasing concern regarding the implications of these super post-Panamax vessels on the container shipping industry.